Evaluating the PEDS:DM Developmental Screening Tool in Zulu and Northern Sotho. Issue 3 (2nd September 2021) - Maleka, Boledi; van der Linde, Jeannie; Graham, Marien; Swanepoel, De Wet
Abstract: Screening of children's developmental milestones is imperative for early identification of developmental delays and early intervention. Translated developmental screening tools increase accessibility and in turn enable timely identification and intervention, which allows children to reach their potential. This quantitative study evaluated the translation accuracy of the Northern Sotho and Zulu Parents Evaluation Development Status: Developmental Milestones (PEDS:DM) in comparison with the English version of the tool. The study was conducted at a regional healthcare facility in South Africa. Stratified convenience sampling was utilised with a total of 546 caregivers representing children from 1 month to 6 years of age. The findings generally reflected a strong correspondence between the English and Northern Sotho, and the English and Zulu PEDS:DM tool, respectively. A few test items in the expressive language domain did not correspond significantly between languages. This could be due to cultural and social differences and should be investigated.